Bread, cement, cactus : a memoir of belonging and dislocation - Zaidi, Annie (Cambridge : Cambridge University Press, 2020)
In this exploration of the meaning of home, Annie Zaidi reflects on the places in India from which she derives her sense of identity. She looks back on the now renamed city of her birth and the impossibility of belonging in the industrial township where she grew up. From her ancestral village, in a region notorious for its gangsters, to the mega-city where she now lives, Zaidi provides a nuanced perspective on forging a sense of belonging as a minority and a migrant in places where other communities consider you an outsider, and of the fragility of home left behind and changed beyond recognition. Zaidi is the 2019/ 2020 winner of the Nine Dots Prize for creative thinking that tackles contemporary social issues. This title is also available as Open Access.
Title from publisher's bibliographic system (viewed on 09 Jun 2020).
Keywords: Zaidi, Annie; Authors, Indic -- 21st century -- Biography; Women authors, Indic -- 20th century -- Biography; Journalists -- India -- Biography